Children as social network actors: A European legal perspective on challenges concerning membership, rights, conduct and liability. Issue 3 (June 2015) - Wauters, Ellen; Lievens, Eva; Valcke, Peggy
Abstract: Recent social science research shows that children from as young as 7 are avid users of Social Networking Sites (SNS) such as Facebook, Twitter, Instagram and Tumblr. The involvement of minor users on SNS platforms raises significant legal challenges, for instance regarding their capacity to enter into a membership agreement, consenting to share or be tagged in photographs and liability for certain actions. This contribution aims to identify relevant legal issues related to SNS use by (young) children and to assess the applicability of existing legal frameworks at European and national level with regard to the capacity to contract, transfer of intellectual property rights, right to image, and the liability of children and parents for certain breaches of legislative provisions or acts that cause damage. The second part contains an exploration of user empowerment mechanisms such as the use of innovative information provision tools or awareness-raising to achieve better informed decision-making by children (and parents) with regard to their SNS use.